EXPECTATION OF A CHILD DURING A PANDEMIC: THE INFLUENCE OF STRESS FACTORS ON THE PRENATAL STRESS OF PARTNERS AND METHODS OF COLLATING IT - Odintsova, O. Yu.; Kryukova, T.L. (Modern Psychology, 2021)
Expectation of a child is a stressful life period, since it determines a number of changes at the organismic, personal, social and sociocultural level in both women and male partners. This condition is referred to as "prenatal stress", the source of which are stressors of different levels - specific for the period of expectation of the child (determined by the course and the specifics of pregnancy), individual (personality-related) and macrosocial. The current epidemiological situation potentially increases the likelihood of developing prenatal stress associated with persistent affective symptoms - anxious, depressive or phobic. This work is focused on the study of fears as a manifestation of prenatal stress, since it is fear, different in content, that is a characteristic feature of our reality. Forced quarantine and fear of infection, combined with limited access to professional medical and social support, heightens the intensity of the experience in couples preparing for parenthood. For an in-depth study of multicomponent stressors that arise during pregnancy and ways of coping with them, an empirical study was carried out in dyads awaiting a child (n = 203). The results indicate that partners are almost equally vulnerable to stressors, but the variations in coping with them are different for women and men. Women show great flexibility in using coping behavior; men have a clear tendency to distance themselves from circumstances. However, in matters of pregnancy, childbirth and health, there are constructive coping methods. The findings indicate the need to develop specific measures aimed not only at women, but also at men.